Pengaruh orientasi masa depan dan dukungan sosial terhadap adaptabilitas karier - Pratama, Muhammad Fikri; Mastuti, Endah; Yoenanto, Nono Hery (Konsorsium Psikologi Ilmiah Nusantara, 2025)
Career adaptability is a crucial aspect for students, particularly those in urban settings, in their career development. Future orientation and social support are known to predict career adaptability. The study explores the impact of future orientation and social support on students' career adaptability. This study involved 300 participants aged 17-24. Utilizing validated scales, including the Career Adapt-Abilities Scale, Future Orientation Scale, and Multidimensional Scale of Perceived Social Support, the research employed multiple regression analysis for data analysis. Results indicate that both future orientation and social support significantly influence career adaptability. Future orientation partially affects adaptability, while social support does not have a partial effect. The findings underscore the importance of future orientation and social support in fostering career adaptability among students. This study offers valuable insights into the factors contributing to students' readiness to navigate challenges in the workplace, shedding light on areas for further exploration in career development research.